Software architecture : 12th European Conference on Software Architecture, ECSA 2018, Madrid, Spain, September 24-28, 2018, Proceedings /: 12th European Conference on Software Architecture, ECSA 2018, Madrid, Spain, September 24-28, 2018, Proceedings. (2018) - Unknown
No abstract available